6 - From the Will to the Field: Parent Participation in Early Childhood Education in Madagascar - Loomis, Colleen; Akkari, Abdeljalil (Africa Development, 2021)
Among state and international actors there is consensus that early childhood education (ECE) is important for future well-being of the child and that parent participation in various school activities is relevant. The willingness of actors in formal education to encourage parents to participate in their school activities varies. There remains a challenge of how to take the will of parents and mobilize it into participation in the field of ECE. In this paper we focus on parents’ participation in ECE in Madagascar, placing that participation within an existing complex context of poverty, former colonialism, contemporary political instability, and international cooperation. We report on data gathered in Anatanarivo, Sakaraha, Toliera, and Betioky to show that there is suspicion between the state and parents in general and that unless current actors (parents, teachers, administrators, NGOs, and government) value parents’ resources and create new ways for parent participation in the extr ctive model of schooling in place, the ECE cannot be enhanced and advanced.